2007
DOI: 10.1111/j.1399-3054.2006.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

The binding of α‐amylase to starch plays a decisive role in the initiation of storage starch degradation in turions of Spirodela polyrhiza

Abstract: Degradation of reserve starch in turions, perennation organs of the duckweed Spirodela polyrhiza, is induced by continuous red light (cR). Irradiation of the turions with this light results in the autophosphorylation of starch‐associated glucan water dikinase (GWD). The ensuing phosphorylation of the starch by this enzyme was proposed to result in the enhanced association of starch‐degrading enzymes to the starch granules and in the initiation of starch breakdown. The present results confirm that the irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…The total phosphate content of deproteinated starch granules was determined colorimetrically by the phosphomolybdate method of Worsfold, Clinch & Casey (1987) as described by Reimann et al. (2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total phosphate content of deproteinated starch granules was determined colorimetrically by the phosphomolybdate method of Worsfold, Clinch & Casey (1987) as described by Reimann et al. (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Deproteinated, lyophilized starch granules were incubated with α ‐amylase partially purified from the turions irradiated for 24 h with continuous R, and were then washed as described by Reimann et al. (2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemnaceae have also been used to solve questions in basic research, e.g. in photosynthesis (Booij-James et al 2009), phytohormone biosynthesis (Rapparini et al 1999) or starch degradation (Reimann et al 2007). Li et al (2004) and Yamamoto et al (2001) reported genetic transformation of some duckweed species, although stable transformation still awaits optimization.…”
Section: Introductionmentioning
confidence: 99%
“…α-Amylase (EC 3.2.1.1, α-(1, 4)-glucan-4-glucanohydrolase), which catalyses the hydrolysis of α-(1, 4) glycosidic linkages in starches, is one of the main enzymes in the digestive tract (Bompard-Gilles, Rousseau, Rougé, & Payan, 1996;Warren, Zhang, Waltzer, Gidley, & Dhital, 2015). Starch digestion by α-amylase involves two steps: binding of the enzyme with starch and a subsequent hydrolysis process; therefore, the adsorption and binding of α-amylase to starch is necessary before the catalytic step can proceed (Patel, Day, Butterworth, & Ellis, 2014) and affects the digestion of starch to some extent (Reimann, Ziegler, & Appenroth, 2007). For the case of starch granules, as their size (0.5-50 µm, radius) is much greater than that of α-amylase (ca 3nm, hydrodynamic radius) (Dhital, Shrestha, & Gidley, 2010;Larson, Day, & McPherson, 2010), the adsorption of the enzyme onto starch granules depends on the number and accessibility of available binding sites on the granules (Warren, Royall, Gaisford, Butterworth, & Ellis, 2011).…”
Section: Introductionmentioning
confidence: 99%